Modern developments in lasing with liquid crystals - Aljohani, Omar; Dierking, Ingo (Frontiers in Materials, 2024)
A review of the recent developments in the field of lasing with liquid crystals (LCs) is presented. After an introduction into the principle of lasing the different relevant liquid crystal phases to the field are introduced, namely the nematic and chiral nematic phase, Blue Phases, twist grain boundary and ferroelectric liquid crystals.The classic examples of liquid crystal lasing are shortly discussed, together with a variety of possibilities for tuning the lasing wavelength, before the modern trends in LC lasing are discussed in detail. These are particularly random lasers, where the effects of nanoparticles, quantum dots and solitons are highlighted, as well as localised surface plasmon resonance. Other modern laser systems that have attracted recent interest, white lasers, whispering gallery mode lasers and those with biological materials, for example cellulose nanocrystals, are also introduced and the latest developments outlined.